2023
DOI: 10.1021/acssuschemeng.3c00764
|View full text |Cite
|
Sign up to set email alerts
|

Vineyard Pruning Extracts as Natural Antioxidants for Biodiesel Stability: Experimental Tests and Preliminary Life Cycle Assessment

Abstract: The control of the oxidative stability of biodiesel and blends of biodiesel with diesel is one of the major concerns of the biofuel industry. The oxidative degradation of biodiesel can be accelerated by several factors, and this is most critical in the so-called second generation biodiesel, which is produced from low-cost raw materials with lower environmental impacts. The addition of antioxidants is imperative to ensure the oxidative stability of biodiesel, and these are considered products of high commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The LCA methodology has been utilized for similar studies evaluating the potential environmental impacts associated with industrial chemical production and comparing the different production approaches based on their level of impacts. Mostly all the sectors are covered: fossil-based industry, , biobased fuels and chemicals, pharmaceuticals, and the synthesis of new catalytic system from earth-abundant metals. Studies presented above, along with several others, established the suitability of the LCA methodology for pinpointing areas where different approaches to the production of chemical compounds excel in terms of environmental performance and the possible areas where process improvement efforts should be concentrated to drive significant environmental gains.…”
Section: Methodsmentioning
confidence: 99%
“…The LCA methodology has been utilized for similar studies evaluating the potential environmental impacts associated with industrial chemical production and comparing the different production approaches based on their level of impacts. Mostly all the sectors are covered: fossil-based industry, , biobased fuels and chemicals, pharmaceuticals, and the synthesis of new catalytic system from earth-abundant metals. Studies presented above, along with several others, established the suitability of the LCA methodology for pinpointing areas where different approaches to the production of chemical compounds excel in terms of environmental performance and the possible areas where process improvement efforts should be concentrated to drive significant environmental gains.…”
Section: Methodsmentioning
confidence: 99%
“…Antioxidants are commonly added to biodiesel to prevent oxidation and increase its shelf life. Research has shown that the addition of natural antioxidants to biodiesel can significantly increase its induction period and improve its storage characteristics [189]. For example, the induction period of the Jatropha biodiesellemongrass oil binary blend was increased by adding antioxidants extracted from peas, coffee, sweet basil, horse gram, and sesame to 4.10, 7.10, 7.74, 8.10, and 9.92 h, respectively, in comparison to the binary blend without antioxidants, in which the induction period was only 2.06 h, as shown in Table 17 [190].…”
Section: -76 Hmentioning
confidence: 99%
“…(a) Changes in peroxide value (PV) of biodiesel doped with antioxidants[189]. (b) Changes of acid values (AV) of biodiesel doped with antioxidants[189].…”
mentioning
confidence: 99%
See 1 more Smart Citation